2014
DOI: 10.9790/2380-07136379
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Molybdenum and Iron on Nodulation, Nitrogen Fixation and Yield of Chickpea Genotypes (Cicer Arietinum L)

Abstract: The present

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 30 publications
10
7
0
2
Order By: Relevance
“…Application of 1.0 kg Mo/ha increased seed yield by 22.1 and 8.0 per cent, respectively, over control and 0.5 kg Mo/ha. The results on seed and straw yields thus confirmed the trend observed in growth and yield attributing characters with application of molybdenum, Shivkumar amd Kumutha (2003), Togay et al, (2008), Valenciano et al, (2011), Gupta et al, (2012, Khan et al, (2014) and Manohar (2014) also observed significant improvement in yield attributes and yield of different crops due to application of molybdenum.…”
Section: Molybdenumsupporting
confidence: 70%
“…Application of 1.0 kg Mo/ha increased seed yield by 22.1 and 8.0 per cent, respectively, over control and 0.5 kg Mo/ha. The results on seed and straw yields thus confirmed the trend observed in growth and yield attributing characters with application of molybdenum, Shivkumar amd Kumutha (2003), Togay et al, (2008), Valenciano et al, (2011), Gupta et al, (2012, Khan et al, (2014) and Manohar (2014) also observed significant improvement in yield attributes and yield of different crops due to application of molybdenum.…”
Section: Molybdenumsupporting
confidence: 70%
“…Further increase in level of Mo to 1.5 kg/ha could not prove beneficial due to low return to investment. The findings of the study found similar to the results reported by Caires and Rosolam (2000) in groundnut, Sharma (2003) in cowpea and Khan et al, (2014) in chickpea.…”
Section: Resultssupporting
confidence: 82%
“…Low availability of water, suboptimal temperatures, long days, excessive salinity, and high amounts of N in the soil greatly affect nodulation in chickpea (Dart et al, 1975;Rupela and Saxena, 1987;Elsheikh and Wood, 1990;Ben Romdhane et al, 2009). On the other hand, SNF in chickpea is negatively influenced by the deficiency of such nutrients as P, Fe, Mo, Co, B, and Zn (Yadav and Shukla, 1983;Yanni, 1992;Khan et al, 2014;Esfahani et al, 2016). Both the nodule number and the diversity of chickpeanodulating rhizobia were adversely influenced by drought in a study by Ben Romdhane et al (2009).…”
Section: Environmental Factors High N Levels and Nutrient Deficiencmentioning
confidence: 96%